Clinical Efficacy of Nutritional Supplements in Atopic Dermatitis: Systematic Review - Isaac Weber; Emily Woolhiser; Noah Keime; Margaret Wasvary; Madeline J Adelman; Torunn E Sivesind; Robert P Dellavalle (JMIR Publications, 2023)
BackgroundAtopic dermatitis (AD), also known as eczema, is a chronic inflammatory skin condition that presents with symptoms of intense pruritus, dryness, and erythema. Dissatisfaction with first-line therapies for AD, the desire to avoid steroids, and the extreme cost of effective biologics have created a demand for alternative treatment options such as oral vitamins and nutritional supplements. ObjectiveThe purpose of this review was to assess the effectiveness of oral nutritional supplements, pre- and probiotics, and vitamin deficiencies and supplements on AD symptomology and clinical course. MethodsWe searched Scopus, PubMed, and MEDLINE (Ovid interface) for English-language articles published between 1993 and 2023. The final search was conducted on June 22, 2023. The search terms comprised the following: "(Atopic Dermatitis or Atopic Eczema) AND (supplement OR vitamin OR mineral OR micronutrients OR Fish Oil OR Omega Fatty Acid OR Probiotics OR Prebiotics OR apple cider vinegar OR collagen OR herbal OR fiber)." ResultsA total of 18 studies-3 (17%) evaluating vitamins, 4 (22%) evaluating herbal medicine compounds, 2 (11%) evaluating single-ingredient nutritional supplements, and 9 (50%) evaluating pre- and probiotics-involving 881 patients were included in this review. ConclusionsOverall, there is weak evidence to support any one nutritional supplement intervention for the alleviation of AD symptoms. Multiple trials (4/18, 22%) showed promise for supplements such as Zemaphyte, kefir, and freeze-dried whey with Cuscuta campestris Yuncker extract. The most evidence was found on the effectiveness of probiotics on the clinical course of AD. Lactiplantibacillus plantarum, Ligilactobacillus salivarius, and Lactobacillus acidophilus specifically showed evidence of efficacy and safety across multiple studies (6/18, 33%). However, larger, more extensive randomized controlled trials are needed to determine the true effectiveness of these supplements on the broader population. Trial RegistrationPROSPERO CRD42023470596; https://tinyurl.com/4a9477u7